PEMIKIRAN ABDULLAH NASHIH ULWAN DALAM BUKU TARBIYATUL AULAD TENTANG TANGGUNG JAWAB PENDIDIK DAN IMPLIKASINYA TERHADAP PENDIDIKAN AKHLAK KONTEMPORER - Shilvie Nur Aeni; Zaenudin, Udin (Program Studi Pendidikan Agama Islam, 2025)
This study examines Abdullah Nashih Ulwan’s thought on the responsibilities of educators as presented in Tarbiyatul Aulad and its relevance to contemporary Islamic education grounded in moral values. The background of this research stems from the declining involvement of parents in their children’s education due to work demands, as well as the challenges faced by teachers in instilling Islamic values amid the pervasive influence of social media and global culture. These conditions have triggered a moral crisis among students, such as diminished respect for teachers, gadget addiction, and declining interest in religious studies. Employing a qualitative approach with a descriptive-analytical method, this research applies content, coherence, and comparative analyses of Tarbiyatul Aulad alongside supporting literature. The findings reveal that Ulwan formulates the responsibilities of educators across seven essential aspects: faith, morality, physical development, intellect, psychology, social relations, and sexuality. This concept remains highly relevant in addressing the challenges of contemporary Islamic education, particularly in developing an educational system oriented toward moral formation as a safeguard against moral degradation. The study concludes that Ulwan’s ideas can serve as a strategic reference for developing Islamic education that is more contextual to the needs of the present era while strengthening the role of educators in shaping a morally grounded generation.